Slavoik - Exploration of transcultural artistic expression on the example of Sámi and Slavic cultures - Siennicka, Michalina (fi=Lapin yliopisto|en=University of Lapland|, 2022)
Art has always been known to transcend national borders; in times of constant migration transculturalism is becoming an increasingly common occurrence in artistic expression. Should cultural belonging define the motifs, style, and topics of one’s art? The presented study is an artistic journey to finding out how far the self-expression can stretch. Through artistic research, Sámi and Slavic weaving patterns were merged into a singular hybrid universe. It has resulted in the exhibition – SLAVOIK, which took place in March 2021, and was later evaluated in the process of cultural immersion. The artistic process has been placed within an ethical grey area, due to its potential of being appropriative of Sámi culture. This led to the development of culturally sensitive ways of engaging in cross-cultural art projects. The research takes into account the ethics of working with Indigenous cultures, cultural appropriation, and the concepts of interaction of cultures: inter- and transculturalism, all from the perspective of a newcomer to Lapland.